Commemorative Notes on Father Ignacio Gordon, S.J. 's contribution to canonical procedural law - Daniel, William L. 1980- (2022)
Father Ignacio Gordon, S.J. zealously served the Church as a proceduralist, teaching procedural law for about 25 years in the Pontifical Gregorian University’s Faculty of Canon Law and advising dicasteries of the Roman Curia about it. Among his main contributions in this area are included his promotion of the ongoing formation of ministers of justice, attention to the best methods of teaching procedural law, his concerns about the celerity of trials in the Church, and the need for the judicial protection of marriage. He offered a particularly indefatigable service to the Supreme Tribunal of the Apostolic Signatura, which was also a special object of his scientific investigation.
Padre Ignacio Gordon, S.J. ha servito con zelo la Chiesa come processualista, insegnando diritto processuale per circa 25 anni nella Facoltà di Diritto Canonico della Pontificia Università Gregoriana e consigliando i dicasteri della Curia Romana su di esso. Tra i suoi principali contributi in questo campo si annoverano la promozione della formazione permanente dei ministri della giustizia, l’attenzione ai migliori metodi di insegnamento del diritto processuale, l’enfasi sul carattere ecclesiale del diritto processuale, le sue riflessioni quanto alla celerità dei processi nella Chiesa, e la necessità della tutela giudiziaria del matrimonio. Offrì un servizio instancabile al Supremo Tribunale della Segnatura Apostolica, che fu anche oggetto speciale della sua indagine scientifica.
Keywords: pars statica; pars dynamica